Barreras fácticas del ejercicio del derecho de alimentos de niñas y niños hijos de padres migrantes que viven en el cantón Ibarra - Gordillo López, Sebastián André (2023)
Ecuador is one of the main destinations of migration from neighboring countries, especially Venezuela and Colombia, although there are also, to a lesser extent, from other latitudes. For this reason, the present study focused its interest on identifying the barriers that hinder the application of the national legal framework regarding the right to food in district in the canton of Ibarra, in the period 2021 and 2022. The general objective was to determine the factual barriers to the exercise of the right to child support of children residing in the canton of Ibarra, children of migrant parents. The approach of this mixed research, socio-legal, inductive deductive method for the search of information in databases based on an intentional sample survey instrument in addition to review and documentary analysis. The conclusions of this study emphasize that the factual barriers identified for the exercise of the right to child support in immigrants in the canton of Ibarra are: 1.- lack of information about custody\; 2.- lack of knowledge of Ecuadorian law and 3.- economic instability for the payment of alimony. The systematization of the regulations for the protection of children's rights is addressed from the Constitution of the Republic of Ecuador (CRE), the Code of Childhood and Adolescence, the COGEP to the 'Ibarra Health and Life' program itself. The analysis within the SATJ did not find judicial processes under the criteria of food, migrant and Ibarra. The diagnosis developed in the survey (n=13) determined that 92.3% affirmed that there is a lack of information and legal resources on the topic addressed\; 61.5% affirmed that due to the lack of information and legal resources, custody rights cannot be exercised.